Balancing managerial and professional demands: school principals as evaluation brokers. Issue 3 (1st January 2016) - Hult, Agneta; Lundström, Ulf; Edström, Charlotta
Abstract : The evaluation trend in the global education field implies new professional challenges for school principals. The purpose of this article is to describe and analyse Swedish school principals' experiences of prevailing evaluations and the implications for the profession. Specifically, we examine: a) how principals respond to evaluations and their consequences in their schools; and b) the implications of the evaluations for the profession in light of professional responsibility and accountability. The interviewed principals are ascribed huge evaluation responsibilities and are in this respect key actors but to some extent are also 'victims' of external pressures. All schools are embedded in a web of evaluation systems. They share the view that evaluations that are useful for improving teaching, student achievement and everyday school life are those conducted close to practice, and involve teachers. Most of them are also aware of the risks for the reduction of the broad goals of schooling and for work overload. The principals express a desire to protect the fundamental values of professional responsibility but the total demands of the local evaluation web have involved a shift in their professional role towards professional accountability.